Impact of attitude, subjective norms, and perceived behavioural control on intention to invest in retail green sukuk among Muslim millennials in Jabodetabek - Ikhsan , Muhammad Ananda; Wulandari, Ries (Journal of Islamic Economics Lariba, 2024)
Introduction Retail green sukuk is an environmentally friendly investment option for millennials. However, there have not been many studies related to this in the context of millennials in big cities in Indonesia. Objectives This research aims to analyse the impact of attitude, subjective norms, and perceived behavioral control in intention to invest in retail green sukuk among Muslim millennials in Jabodetabek. Method This research uses the PLS-SEM (Partial Least Square Structural Equation Modeling) which presents the results of regression analysis relating to testing the relationship between endogenous and exogenous variables. A total of 183 Muslim millennials participate in this research by fulfilling an online questionnaire. Results The results of this research show that these three variables significantly influence Green Sukuk investment interest among Millennial Muslims in Jabodetabek, with a significance value of attitude of 0.669, subjective norm of 0.213, and perceived behavioral control of 0.030. Implications Governments or other corporations issuing retail green sukuk instruments should focus more on promoting their green initiatives. This will create a positive attitude among millennial investors toward Retail green sukuk instruments. Originality/Novelty This study provides insights into the intention to invest in environmentally friendly financial product among Muslim millennials living in large cities in Indonesia.